Processes for regulating interconnection rates in India and South Africa - Chetty, Sagadhevan (My University, 2013)
South Africa‟s high telecommunication costs are attributed partly to high interconnection rates. High costs negatively impact developmental objectives. This paper analyses the processes engaged in by ICASA in regulating interconnection rates, using a qualitative case study methodology. Enabling legislation, regulatory administration and rules and the bringing to bear of regulatory rules on institutions are stages of regulatory processes that are examined. Perspectives are taken from processes executed by TRAI, India‟s regulatory authority. South Africa followed a market review process which contrasts with India‟s cost-based process. South Africa‟s process although arduous did not achieve the desired result of establishing cost based rates. The root cause is attributed to a combination of factors that include an onerous market review process prescribed by the ECA, institutional problems at ICASA and a politically driven process that ran alongside and engulfed the process managed by ICASA. India‟s process meanwhile has yielded some of the cheapest telecoms retail rates in the world. Gaps exist between processes in the two countries and lessons learnt provide an improved understanding of South African shortcomings.
Keywords: Telecommunication; Rates; India; South Africa